A Computational and Experimental Study on a Harsh Environment LED System for Vehicle Exterior Lighting Applications - Khosroshahi, Saati F.; Tufekci, C. S.; Arik, M. (IEEE, 2014)
Effect of compact thermal packaging approaches and challanges are investigated for a next generation automotive LED lighting. A challenging three-purpose in one (3il) highly packaged light emitting diodes (LEDs) lighting system has been studied computationally and experimentally. A tightly packed light engine printed circuit board (PCB) with both LEDs and electronics in a very hermetically sealed enclosure close to the vehicle engine department pose significant thermal and mechanical challenges for the thermal design as well as optical considerations. Challenge is due to local high ambient temperatures and aggressive operating conditions. Finite element based computational models have been developed first to study a single package thermal performance, and then followed by system level computational fluid dynamics (CFD) models. Later, a series of experiments and analytical studies have been performed for validation of computational results. It is found that interface layer at the package poses significant bottlenecks for meeting the design requirements. System level CFD models showed that having a two-sided flame retardant (FR4) based board causes local hot spots that need innovative system level cooling solutions.
Keywords: automotive; light emitting diode; single LED package; conduction; junction to solder point resistance; junction to ambient resistance; system modeling; Engineering